A Chemical Inhibitor of the Skp2/p300 Interaction that Promotes p53‐Mediated Apoptosis. Issue 2 (23rd November 2015) - Oh, Misook; Lee, Ji Hoon; Moon, Heejo; Hyun, Yu‐Jung; Lim, Hyun‐Suk
Abstract: Skp2 is thought to have two critical roles in tumorigenesis. As part of the SCF Skp2 ubiquitin ligase, Skp2 drives the cell cycle by mediating the degradation of cell cycle proteins. Besides the proteolytic activity, Skp2 also blocks p53‐mediated apoptosis by outcompeting p53 for binding p300. Herein, we exploit the Skp2/p300 interaction as a new target for Skp2 inhibition. An affinity‐based high‐throughput screen of a combinatorial cyclic peptoid library identified an inhibitor that binds to Skp2 and interferes with the Skp2/p300 interaction. We show that antagonism of the Skp2/p300 interaction by the inhibitor leads to p300‐mediated p53 acetylation, resulting in p53‐mediated apoptosis in cancer cells, without affecting Skp2 proteolytic activity. Our results suggest that inhibition of the Skp2/p300 interaction has a great potential as a new anticancer strategy, and our Skp2 inhibitor can be developed as a chemical probe to delineate Skp2 non‐proteolytic function in tumorigenesis. Abstract : Skp2 inhibitor: The discovery of a chemical inhibitor of the Skp2/p300 interaction is reported. The inhibitor is able to specifically inhibit non‐proteolytic activity without affecting Skp2 proteolytic activity. Thus, the inhibitor can be developed as a chemical probe of Skp2 non‐proteolytic function during tumorigenesis.